Qualidade do queijo de coalho comercializado em Governador Dix-Sept Rosado- RN - Costa, Fransuênia Silva da (Universidade Federal Rural do Semi-Árido, 2017)
The coalho cheese is traditionally handcrafted and the lack of Good Manufacturing Practices at the time of preparation can influence the quality of this product, resulting in products unfit for human consumption. The objective of this work was to evaluate the quality of rennet cheese marketed in the city of Governador Dix-Sept Rosado - RN. For this, 14 samples of rennet cheese, without inspection seal, of different establishments were analyzed with coliforms between 35 and 45ºC, Coagulase positive Staphylococcus, Salmonella spp. and also pH and acidity. It was found that all the samples presented disagreement with the legislation regarding Staphylococcus coagulase positive at eight regarding the standards with coliforms at 45ºC. There was no evidence of Salmonella spp. in none of the samples. PH and acidity varied from 3.97 to 5.01 and 0.23 to 0.9%, respectively. Therefore, the high population of these microorganisms indicated the low hygienic quality, presenting risks the health of consumers.
Monografia
Keywords: Higiene dos alimentos; Qualidade microbiológica; Acidez; Food hygiene; Microbiological quality; Acidity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA